Alas Kandung-based science learning tools to optimize students’ critical thinking skills - Novita Ratnasari; S. Sarwanto; Baskoro Adi Prayitno (University of Muhammadiyah Malang, 2020)
Critical Thinking Skills (CTS) are the crucial skills required by nowadays generation in dealing with the 21st Century challenges. Yet, the researches focused on higher order thinking skills are still limited. This study aimed to analyze the effect of Alas Kandung-based science learning tools on students’ CTS. The research design was pretest and post-test with non-equivalent control group. The treatment given in experimental class was the implementation of Alas Kandung-based science learning tools, while the control class was taught using common method used by the teachers. The results of this study indicated that the students’ CTS in experimental class was significantly higher than the control class [F(1,47) = 11.672, p = 0.001]. In conclusion, the Alas Kandung-based science learning tools is effective in improving students’ CTS.